Multifunctional Superhydrophobic Coatings for Aluminum and Magnesium Alloys: Applications and Performance - Review - Hanaa Soliman; Rongling Zhang; Xialong Cai; Wei Feng; Alanood A. Alsarayreh; Awesar A. Hussain; Salih Alsadaie (Journal of Techniques)
The manufacturing of aerospace, automotive, and defense systems depends on aluminum and magnesium alloys because they provide low density, a high strength-to-weight ratio, and easy machining capabilities, which result in better fuel efficiency, increased payload capacity, and enhanced maneuverability in aerospace and ground-based military platforms. Despite these advantages, both alloys suffer from poor corrosion and wear resistance, which restricts their use in harsh environments and poses risks to the performance and reliability of military systems. Surface modification technologies provide immediate solutions to these problems through superhydrophobic coatings emerging as a promising approach. The coatings deliver water repellency while simultaneously improving self-cleaning capabilities, antifouling properties,  drag reduction,  anti-icing features, corrosion protection, and wear resistance. Recent studies have made substantial advancements in designing and manufacturing superhydrophobic surfaces. The current methods for preparing superhydrophobic surfaces require complicated procedures, expensive equipment, and strict processing conditions, which create challenges for industrial-scale implementation. This review presents two representative studies for aluminum and two for magnesium alloys, with emphasis on preparation methods, surface morphology, and performance outcomes. The aim is to clarify the strengths and limitations of these coatings and support their development in practical applications that require durability, corrosion resistance, and multifunctionality. It compares their performance across different substrates while considering their effectiveness for corrosion resistance, anti-bacterial, anti-icing, and friction resistance with self-cleaning performance.